Regional High-Level Multi-stakeholder Policy Dialogue - Whitfield, Stephen; Mavuso, Terrence; Sarku, Rebecca; Nkanyani, Shiluva Chauke (Food, Agriculture and Natural Resources Policy Analysis Network, 2024)
The 2024 FANRPAN Regional High-Level Multi-stakeholder Policy Dialogue, held in Lilongwe, Malawi, aimed to address the complex challenges facing Africa's agriculture and food systems. The dialogue focused on fostering innovative policy frameworks, strategies, and actions to enhance agricultural productivity, sustainability, and resilience. It sought to explore the role of digital technologies, research, and innovation in transforming agri-food systems and to analyse the socio-economic implications of various policy interventions on smallholder farmers, rural communities, and marginalized groups. Additionally, the event promoted regional collaboration and knowledge exchange among policymakers, researchers, and practitioners to ensure cohesive and effective agricultural strategies across the continent.